Pandemics, politics, and society : critical perspectives on the Covid-19 crisis - Delanty, Gerard, 1960- (De Gruyter, 2021)
This volume is an important contribution to our understanding of global pandemics in general and Covid-19 in particular. It brings together the reflections of leading social and political scientists who are interested in the implications and significance of the current crisis for politics and society. The chapters provide both analysis of the social and political dimensions of the Coronavirus pandemic and historical contextualization as well as perspectives beyond the crisis. The volume seeks to focus on Covid-19 not simply as the terrain of epidemiology or public health, but as raising fundamental questions about the nature of social, economic and political processes. The problems of contemporary societies have become intensified as a result of the pandemic. Understanding the pandemic is as much a sociological question as it is a biological one, since viral infections are transmitted through social interaction.-In many ways, the pandemic poses fundamental existential as well as political questions about social life as well as exposing many of the inequalities in contemporary societies. As the chapters in this volume show, epidemiological issues and sociological problems are elucidated in many ways around the themes of power, politics, security, suffering, equality and justice. This is a cutting edge and accessible volume on the Covid-19 pandemic with chapters on topics such as the nature and limits of expertise, democratization, emergency government, digitalization, social justice, globalization, capitalist crisis, and the ecological crisis. Contents Notes on Contributors Preface Gerard Delanty1. Introduction: The Pandemic in Historical and Global Context Part 1 Politics, Experts and the State Claus Offe2. Corona Pandemic Policy: Exploratory Notes on its 'Epistemic Regime' Stephen Turner3. The Naked State: What the Breakdown of Normality Reveals Jan Zielonka4.-Who Should be in Charge of Pandemics? Scientists or Politicians? Jonathan White5. Emergency Europe after Covid-19 Daniel Innerarity6. Political Decision-Making in a Pandemic Part 2 Globalization, History and the Future Helga Nowotny7. In AI We Trust: How the COVID-19 Pandemic Pushes us Deeper into Digitalization Eva Horn8. Tipping Points: The Anthropocene and COVID-19 Bryan S. Turner9. The Political Theology of Covid-19: a Comparative History of Human Responses to Catastrophes Daniel Chernilo10. Another Globalisation: Covid-19 and the Cosmopolitan Imagination Frédéric Vandenberghe & Jean-Francois Véran11. The Pandemic as a Global Total Social Fact Part 3 The Social and Alternatives Sylvia Walby12. Social Theory and COVID: Including Social Democracy Donatella della Porta13. Progressive Social Movements, Democracy and the Pandemic Sonja Avlijaš14. Security for Whom? Inequality and Human Dignity in Times of the Pandemic Albena Azmanova15.-Battlegrounds of Justice: The Pandemic and What Really Grieves the 99% Index